Socialization as a Way for Improving Student Morality Behavior - Sharon Campbell- Phillips (SIASAT, 2020)
This paper explores whether the college level educational institutions in Bangladesh ensure scopes enough to teach, learn and exercise morality behaviors from the part of the learners. The data were collected from the fifty participants of targeted population of a ‘X’ college of Bangladesh. A semi-structured questionnaire was used as data collection instrument and both qualitative and quantitative data were intended to receive. The sample was selected through snowball sampling procedure from the ‘Y’ department of ‘X’ college. ‘Y’ department was selected randomly. Then, data was analyzed on the basis of ratio and nominal scale to analyze the data.